An Investigative Survey on Technological Risks in Software Projects - Dantas, Emanuel; Sousa, Ademar; Albuquerque, Danyllo; Lima, Luís Henrique (Anais do Workshop Brasileiro de Engenharia de Software Inteligente (ISE), 2023)
A project risk is an uncertain event or condition that, if achieved, affects at least one of the project’s objectives. Technological risks have different characteristics from ordinary risks. These risks are typically more uncertain and subjective. Unfortunately, the literature is scarce regarding the presentation of technological risks. To fill this gap, we conducted a Survey with specialists in the field to assess the main risks and their impacts on software projects. As a result, three risks were cited by more than 70% of experts:“Failed to perform asynchronous tasks”, “Integration with plugins failed”, and “Loss of connection in HTTP request”. Our study presents an emerging study, as future work a case study is planned to collect more information from the industry.